STATUS SOSIAL NON-MUSLIM DI TIMUR TENGAH - Ahmad Naufal Dzulfaroh (IAIN Purwokerto, 2019)
This study aims to find detailed data on non-muslim social status in the Middle East, particularly the social status of Coptic Christian groups in Egypt, Christian Maronites in Lebanon, Christian in Sudan as well as Jewish communities in Egypt, Iraq and Iran. The research method used in this research is descriptive qualitative through literature review. The authors analyzed matters relating to the existence of groups, social and political status of non-muslim communities in the Middle East. As for the results of this analysis is first, non-muslim existence in the Middle East as a whole occupies a position as a minority group. This is due to the long history of the Islamic journey that has captured the entire Middle East region and the diaspora of the non-muslim population to the West. Second, in general, non-muslim groups in the Middle East are able to co-exist well with the majority. However, in certain situations minority groups are often subjected to several acts of terror, such as killing and assaulting houses of worship. Third, judging from the right received by non-muslim groups in the Middle East as citizens, only Sudanese Christian groups, Jewish Communities in Iraq and Iran are received discriminatory treatment. Fourth, politically, only the Egyptian and Christian Copts of Sudan received discriminatory treatment from the government, both political and parliamentary. Keywords: Social Status, Non-muslim, Middle East